Development of web based for POZI Catering reservation system using Drag and Drop (DnD) feature / Muhammad Izzul Aiman Ismail - Ismail, Muhammad Izzul Aiman (2017)
POZI Catering that are located in Gong Badak, Kuala Terengganu. They are having a problem when client making a reservation. POZI Catering does not having any computerized system that could help them to overcome this problem. POZI Catering also does not keep customers information in the computerize system. In addition, they also having a problem in designing event layout which is they need to hired a canopy company to handle it. Then, this project is target to develop a project POZI Catering Reservation using Drag-n-Drop (DnD) Feature for client to manage their reservation while staff to manage the event information and event layout. The clients having difficulties according to the POZI Catering schedule which is available and unavailable schedules. The project was fragmented into five phases which is Introduction, Literature Review, Methodology, Result and Analysis and Conclusion and Recommendation. The methodology that has been used in the project is Waterfall Model. It can be carried out and completed sequentially with no overlap. The features were reviewed and compared with several web features which is Canvas Drawing, Scalable Vector Graphical(SVG) and Drag-and-Drop (DnD) was selected for this project. The requirements for this project was collected by interview of the stakeholder. It was analyzed using CRUD technique and it was documented in Software Requirement Specification (SRS). The system design and structures were made using Java Eclipse software and it was documented in a Software Design Document (SDD). When the system was in the development phase, the Drag-n-Drop feature has been implemented in the system and it has been tested by researcher to confirm whether the given solution in designing event layout problem. The system is to be believed that it could solved the problem but due to limited of time, the system could not give the solution but the reservation still can be made using the system. The lecturers also were given a test to the system but the lecturers were incapable to give their responses as the researcher time was restricted. There are still some yet to come work need to be finished to fully develop the system.